An exploratory observational study of the seasonal changes of body composition, bone parameters, testosterone, and cortisol in Spanish male professional soccer players - Almodóvar-Fernández, I.; Real-Fernández, A.; Sánchez-Thevenet, P.; Usó-Vicent, H.; Muñoz-Macho, A.; Arasa, J.; González-Moret, R.; Ibañez, L. (European Journal of Human Movement, 2025)
Body composition (BC) and bone quality are critical factors in the reduction of sport-related injuries and in the improvement of physical performance. Furthermore, testosterone and cortisol may influence these parameters. The aim of this work was to examine changes in total and regional bone mineral density (BMD), bone mineral content (BMC), lean mass (LM), fat mass (FM), total cortisol (tC) and total testosterone (tT) levels of professional soccer players of the Spanish professional league over 2 consecutive seasons in the following stages: start-preseason, start-season, mid-season, and end-season. An observational study was conducted with twenty-six male players (age = 26.9 ± 4.5 years). Statistical analyses included repeated-measures ANOVA to assess changes across the four time points, with post hoc tests corrected using the Bonferroni method. Pearson`s correlation coefficient (r) was used to evaluate associations between variables. FM was more responsive to physical activity across a soccer season than the other parameters analyzed. Results revealed an association between tT variations and changes of trunk FM and LM (p<0.05). Therefore, soccer season leads to variations in BC and serum biomarkers of the players that must be considered to improve players performance and prevent injuries.